Dukungan Sosial Sebagai Prediktor Burnout Wanita Karyawan Pabrik Tinggal Bersama Mertua - Elisa Anggraini; Christiana Hari Soetjiningsih (Universitas Darul Ulum, 2025)
Burnout is a fatigue syndrome experienced by someone either physically or mentally that occurs due to excessive demands of a job. Burnout is one of the problems that can occur in a woman who works as a factory employee and lives with her in-laws. in addition to reducing or preventing the emergence of burnout, social support can be provided from both her husband and her in-laws. Individuals who experience burnout often show a cynical attitude and lack of interest in a job, and individuals feel useless because individuals feel that they are not competent in carrying out their work. The purpose of this study was to determine the social support of husbands and social support of in-laws together as predictors of burnout in female factory employees living with their in-laws. This study used an accidental sampling technique with a multiple linear regression analysis design method. The results showed that there was an influence between social support from husbands and social support from in-laws together as predictors of burnout in female factory employees living with their in-laws, which means that the higher the social support of husbands and in-laws given, the smaller the influence of burnout and vice versa.